Legal Protection for Personal Data Leaks and Its Implications for Citizens' Privacy Rights Within The Framework of The Indonesian Legal State - Huda, Uu Nurul; Astarudin, Tatang; Nasution, Muhammad Irsan; Khozin, Ahmad Abdul; Irsan, Muhammad (Universitas Negeri Gorontalo, 2026)
This study aims to examine the problem of personal data leakage in Indonesia, with a focus on the factors causing the leakage, its impact on citizens' privacy rights, and legal protection measures taken by authorized institutions and electronic system organizers (ESE) within the framework of the Indonesian rule of law.This study uses a qualitative descriptive-analytical approach, combining empirical data from field interviews with legal analysis. Key stakeholders from government institutions responsible for the management and protection of personal data were interviewed, and existing regulations, such as the Personal Data Protection Law and Permendagri No. 17/2020, were analyzed to understand the effectiveness of existing legal protection. Research findings show that data breaches in Indonesia are caused by inadequate data security infrastructure, limited expertise at the local level, and inconsistent implementation of national regulations. Although regulatory frameworks such as ISO 27001 certification are in place, a lack of resources and training in local governments hampers effective data protection. Coordination between central and local governments is essential, but faces challenges in ensuring uniform data management practices and protecting personal data from external threats.